The Role of Management Analysis in Identifying the Problems of Combustion Stoppage During the Production Process of Gas Lembam in the Inert Gas Generator - M. Aji Luhur Pambudi; Ali Khamdilah; Santhi Wilastari (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
The reliability of the inert gas generator system plays an important role in maintaining operational safety and combustion stability in shipboard systems. However, operational disturbances often occur due to failures in the combustion detection process, particularly in the flame eye detector component that monitors flame intensity during ignition and operation. These disturbances can cause interruptions in the combustion process and reduce the performance of the inert gas generator system. Therefore, this study aims to analyze the utilization of management analysis in identifying and mapping problems occurring in the inert gas generator in order to determine the root causes and appropriate corrective actions. This research employs a descriptive qualitative method to obtain comprehensive data related to the operational performance of the inert gas system. The research process begins with systematic problem mapping followed by field observations to collect real operational data from the inert gas generator system. Data collection is conducted continuously to identify the primary cause of the disturbance. The analysis focuses on several aspects, including the set-point regulation of light intensity readings detected by the flame eye detector, the timer set-point requirements during ignition, and the system’s response to combustion light intensity. The results indicate that failures in the flame eye detector reading process and improper set-point timer configuration significantly influence the interruption of the combustion process in the inert gas generator. Predictive analysis assists in narrowing down the potential causes and identifying the most critical factors affecting system performance. These findings highlight the importance of systematic management analysis in diagnosing operational problems and improving the reliability of inert gas generator systems.